Urine biochemistry to predict long‐term outcomes in fetuses with posterior urethral valves. (27th September 2018) - Dreux, Sophie; Rosenblatt, Jonathan; Moussy‐Durandy, Amélie; Patin, Franck; Favre, Romain; Lortat‐Jacob, Stephen; El Ghoneimi, Alaa; Oury, Jean‐François; Deschenes, Georges; Ville, Yves; Heidet, Laurence; Muller, Francoise
Abstract : What's already known about this topic? In fetuses with lower urinary tract obstruction, prenatal counseling with regard to long‐term renal function is an unmet challenge. The literature on the predictive value of fetal urine analysis is controversial. What does this study add? In a cohort of 89 children affected by posterior urethral valves, and who reached 10 years of age, multivariate analysis of fetal urinary markers predicted renal function with 93% sensitivity and 71% specificity. Abstract: Objective: Because the literature on the predictive value of fetal urinalysis is controversial in fetuses with lower urinary tract obstruction, we determined the best model of fetal urine biochemical markers correlated with long‐term postnatal renal function based on glomerular filtration rate (GFR). Method: This retrospective study concerned 89 fetuses with lower urinary tract obstruction and their renal function after 10 years of age. We correlated fetal urine biochemical markers (total protein, β2‐microglobulin, sodium, chloride, glucose, calcium, and phosphorus) with GFR at 10 to 30 years of age in 89 patients with posterior urethral valves. We defined five stages of chronic kidney disease (CKD). Results: Of the 89 patients, 18 (20%) are 20 years old or over. Postnatal renal function was good in 67.4% (GFR > 60 mL/min/1.73 m 2 ) and poor in 17% (GFR < 30 mL/min/1.73 m 2 ). All fetal urine markers differed between CKD stage 1 + 2 and CKD stage 4 + 5 ( P  < 0.001). β2‐microblobulin showed an 87% sensitivity for a 72% specificity. A combination of β2‐microglobulin and chloride gave the best results (93% sensitivity and 71% specificity) versus amniotic fluid volume (80% sensitivity and 73% specificity). Conclusion: Fetal urine biochemistry predicts long‐term (10‐30 years) postnatal renal function.